The art book for children. - Ruggi., Gilda Williams, ....- (London : Phaidon, 2005)
Can dressing up be art? How do you paint feelings? Why did Giuseppe Arcimboldo choose a grocer's shop to find his inspiration? How do you make an Alberto Giacometti? Can you paint a noise? Why did Jeff Koons make a giant sculpture from 70,000 plants? This book explores the choices and attitudes of thirty different artists. It helps stimulate children's own creativity and imagination by asking them to wonder why artists create things in the way that they do. It explores the various ideas, meanings, roles and functions of art by looking at painting, sculpture, photography and prints and helps develop children's understanding of colour, form, texture and pattern. Simple, clear and fun, it is an ideal tool for teachers and parents, as well as a perfect introduction to all those approaching art for the first time. This book is the offspring of The Art Book, one of the best-selling and most recognizable art books ever published. A short introduction explaining the selection of artists and how the book is best used 30 double-page spreads, each dedicated to one artist, are in a clear, repeated design format. Each artist's spread includes: - a large, full-colour reproduction - all key factual details regarding the artwork and the artist - highly readable, short text that aims at directing the child (and his or her adult reader) to look closely at the artwork, and invites a personal response. Also explained in this text are the people, story or ideas behind the work - cross referencing system helping the reader to make links from one picture to another - a brief artist's biography - a thumbnail portrait of the artist. A glossary of key words
Keywords: Kunst -- Encyclopedieën